Key Elements for Observing and Evaluating Online Teaching - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2015)
Observation and evaluation of teaching is an integral part of faculty evaluation, reappointment, and tenure processes. This presentation focuses on protocols for observing and evaluating online teaching and uses case studies to highlight different approaches and artifacts. Chairs will consider the approaches’ pros and cons and identify essential elements.
Keywords: Online; teaching; evaluation; faculty; RTP